2020
DOI: 10.26452/ijrps.v11i4.3120
|View full text |Cite
|
Sign up to set email alerts
|

Functional Strength Training In Children With Spastic Cerebral Palsy

Abstract: To find out functional strength training exercise on improving gross motor function among the children with spastic hemiplegic cerebral palsy children. Single group pre-experimental research design. The most common cause of movement disability in infancy is cerebral palsy. Cerebral palsy patients have impairments such as spasticity, low muscle strength and selective motor control in their body function. Such deficiencies may limit activity performance and participation in everyday life. Improving and optimisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Prudente et al (2010) observed notable enhancements in gross motor functions following such interventions, underscoring the potential of targeted training programs to facilitate significant developmental gains (Prudente et al, 2010). Similarly, comprehensive reviews by Liang et al (2021) and Sathish et al (2020) have systematically evaluated the effectiveness of various interventions, including exercise programs and strength training, in fostering improvements in gross motor functions among this population (Liang et al, 2021;Sathish et al, 2020). These studies collectively highlight the critical role of structured and specialized rehabilitation efforts in mitigating the impact of CP on gross motor skills.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Prudente et al (2010) observed notable enhancements in gross motor functions following such interventions, underscoring the potential of targeted training programs to facilitate significant developmental gains (Prudente et al, 2010). Similarly, comprehensive reviews by Liang et al (2021) and Sathish et al (2020) have systematically evaluated the effectiveness of various interventions, including exercise programs and strength training, in fostering improvements in gross motor functions among this population (Liang et al, 2021;Sathish et al, 2020). These studies collectively highlight the critical role of structured and specialized rehabilitation efforts in mitigating the impact of CP on gross motor skills.…”
Section: Introductionmentioning
confidence: 95%
“…Each session, lasting between 75 to 90 minutes, is designed to progressively challenge and develop the child's motor skills in a supportive and stimulating environment. The sessions incorporate a mix of structured activities, individualized exercises, and playful interactions to ensure engagement and maximize outcomes (Sathish et al, 2020).…”
Section: Integrated Gross Motor Skills Programmentioning
confidence: 99%